Equation Model Development of Factors Affecting Purchase Intention through Electronic Commerce of consumer groups in Bangkok - Cherdboonmuang, Suradchada; Tansuwan, Kittibhop (Journal of Humanities and Social Sciences Thonburi University, 2023)
The purpose of this research was to study 1) the level of priority of factors that affect purchase Intention through Electronic Commerce of consumer groups in Bangkok 2) the equation model development of factors affecting the purchase Intention through Electronic Commerce of consumer groups in Bangkok. There was a quantitative research. Data were collected from 400 customers who used to shop through e-commerce and lived in Bangkok. The statistics used for data analysis were mean, standard deviation and Multiple Regression Analysis. To analyze by objective, the results revealed that factors affecting the purchase Intention through Electronic Commerce of consumer groups in Bangkok as followed; 1) The most priority factors was a Driven Shopping via E-Commerce (E-DS) ( = 4.76, S.D.= 0.32). For the reason that it was impressive and easy to find products’ information and services providing in social networks such as Facebook, Line, YouTube, etc. through marketing technology media including advertising, public relations and sales promotion etc. The other was Customer Satisfaction via E-Commerce (E-CS) ( = 4.73, S.D.= 0.32). There were the design of instructions providing for users to E-Commerce servicing. Moreover, users would recommend others to purchase through E-Commerce in any opportunities. 2) The equation model was from the multiple regression correlation coefficients that were then written as a forecasting equation in following: E-PI= 0.902 + 0.356(E-PQ) + 0.228(E-CS) +0.120(TAM) + 0.103(E-DS). It was a forecasting factor that affects consumers' purchase intentions through E-Commerce in Bangkok with a predictive power of 42.8 percent (R2=.428); a standard error from forecasting at (+/-) 0.264 with a statistical significance level of 0.05.